2019
DOI: 10.1002/adma.201808181
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐Up Grown 2D InSb Nanostructures

Abstract: Low‐dimensional high‐quality InSb materials are promising candidates for next‐generation quantum devices due to the high carrier mobility, low effective mass, and large g‐factor of the heavy element compound InSb. Various quantum phenomena are demonstrated in InSb 2D electron gases and nanowires. A combination of the best features of these two systems (pristine nanoscale and flexible design) is desirable to realize, e.g., the multiterminal topological Josephson device. Here, controlled growth of 2D nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
“…On the other hand, these types of synthesis have in most cases been performed on planar, unpatterned substrates, therefore leading to a random distribution of the NWs . The growth of ordered arrays of nanocrystals of different chalcogenide alloys, including Sb 2 Te 3 , by selective MOCVD growth has been demonstrated on low aspect‐ratio lithographically patterned (≈100 nm size) templates and on substrates locally treated by oxygen plasma, as well as using Au nanodeposits as catalyzers exploiting the vapor–liquid–solid mechanism . For what concerns high‐aspect‐ratio chalcogenide nanostructures, the growth of Te‐rich Sb 2 Te 3 NWs exploiting the vapor–solid mechanism on substrates patterned with pores of diameter ≈50 nm and height ≈100 nm has been explored .…”
Section: Introductionmentioning
confidence: 99%
“…Further work could also aim at optimizing the growth conditions to increase the yield of nanosails as in refs. .…”
Section: The Different Observed Phases Of Zn3as2 Their Space Group mentioning
confidence: 99%
“…However, to build a device in which braiding of topological quantum states, such as Majorana fermions, can be conveniently performed and thus topological quantum computations can be designed and realized, it could be inevitable to move from single-nanowire structures to multiple-nanowire 20,21 and twodimensional (2D) planar quantum structures [22][23][24] . Recently, highquality InSb/InAlSb heterostructured quantum wells 25,26 and freestanding InSb nanosheets [27][28][29][30] have been achieved by epitaxial growth techniques. In comparison with InSb/InAlSb quantum well systems, the free-standing InSb nanosheets have advantages in direct contact by metals, including superconducting materials, in easy transfer to different substrates, and in convenient fabrication of dual-gate structures.…”
Section: Introductionmentioning
confidence: 99%